Coarse sediments in Northern Apennine peat bogs and lakes: New data for the record of Holocene alluvial phases in peninsular Italy. (August 2014) - Giraudi, Carlo
This research was conducted in the Northern Apennines, in the upper valleys of the Cedra River and Parma River, occupied by glaciers during the last glacial maximum. The stratigraphy, the dating and the interpretation of the environmental significance of alluvial deposits interbedded between lacustrine sediments are reported. The data provide an overview of the periods of enhanced alluvial activity that occurred after the glacial retreat in the Apennine chain. The alluvial phases and the periods of environmental stability varied in frequency and length during the Holocene. In particular, starting from the beginning of the Apennine Neoglacial (about 4.2 kyr BP), the events became much more frequent but shorter. The elapsed time between alluvial phases (i.e. the length of the phases of stability) was greater during the Early Holocene, probably because of the values of insolation: when the insolation in July was lower, the length of the phases of stability was greater. Despite the uncertainty in the dating of some events, it is likely that many alluvial phases, later than about 8.5 kyr BP, started during ice rafted debris events in the North Atlantic. The overall analysis of the alluvial sedimentation indicates that periods of more frequent floods are associated with times of rapid climate change and not only with cool periods. The current increase in floods, linked to the ongoing climate change, confirms the data obtained from Holocene sediments.